Smoking cessation for hospital inpatients - Bickerstaffe, Gary (BMJ Qual Improv Rep, 2014)
People who smoke make up a significant number of those admitted to hospital (NICE 2014). Being admitted to hospital can present a unique opportunity to attempt to stop smoking. Many smokers find quitting very difficult (Rigotti et al 2007), in large part due to them living and working in environments that contain many cues and triggers associated with nicotine consumption and smoking behaviours. Hospitals generally do not contain such environmental prompts to smoke. In the community, smokers have access to numerous types of support including GP's, pharmacies and Stop Smoking Services (SSS). Once admitted to hospital access to such support is significantly diminished. Given that many patients may be highly motivated to attempt to stop smoking due to heightened concerns about their health and being in an environment not associated with their smoking habits, it seems prudent to ensure there is access to all the levels of smoking cessation support available outside of the hospital. Not providing such support neglects implementing an evidence based, cost-effective health intervention in a major health setting (NICE 2014). A SSS pathway was designed that enabled existing hospital healthcare staff to be trained to identify patients that smoke, ask if the patient is considering quitting or abstaining whilst in hospital. If motivated to quit or abstain, to complete an assessment. This being based around dependence to nicotine and motivation to quit. Access to all available stop smoking medications should be included. Medication should only be provided alongside some level of motivational support up to discharge. Training core staff was felt to be the best option. They are available outside of office hours and access hospital systems such as pharmacy more readily than satellite staff. On discharge the patient is ‘handed over’ to SSS for continued contact and support once at home. Over 200 staff are trained to complete the assessment and support inpatients to stop or abstain. Approximately 30-35 referrals are made to the local SSS each month, the quit rate at 4 weeks averaging around 40–45%. Most referrals are seen from cardiology and respiratory. All hospital departments should identify staff to be trained to offer cessation support to their patients .